Determination of Some Physical Fitness and Body Composition Characteristics of Young Bocce Players in Turkish National Team - Mutlu Türkmen; Ali Özkan; Murat Kul (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Bocce is gaining popularity throughout the world and is a game that is dominated by aerobic and anaerobic power-capacity, endurance, and strength and body composition. These are all important factors in order to reach a successful performance in Bocce. The purpose of this study was to determine some physical fi tness and body composition characteristics of young Bocce players in Turkish national team. A total of 26 six (14 female age 21.00±8.47 and 12 male age 19.58±3.34) Bocce players from National Team of Turkey participated in this study voluntarily. Subjects' height, body weight, body mass index and body fat percentage were measured. Body fat percentage was determined by Yuhasz formula, and isometric dynamometer was used in order to determine knee, back, grip strength. The sit and reach test was used for the determination of fl exibility. Results indicated that Bocce players have normal body mass index and body fat percentage and ectomorphy-mesomorphy properties. Results of the isometric knee, back, right-left grip strength values of Bocce players was 77.54±24.8 kg, 90.54±26.85 kg and 36.10±9.91-34.27±10.08 respectively and have normal fl exibility (32.5±5.86). As a conclusion, the fi ndings of the present study indicated that Bocce players have almost average body fat percentage, isometric strength and fl exibility function.